UPAYA MENUMBUHKAN KREATIVITAS ANAK DENGAN PERMAINAN MATEMATIKA - achmad hidayatullah (Pedagogi : Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2016)
The  development  of  more  advanced  affects  parents.  Most  parents  wished  for  her clever  counting  etc.  Because  demand  is  so  great  would  be  a  problem  if  the  expectations imposed  on  early  childhood  in  a  span  of  2‐7  years.  Educational  institutions  also  as playgroup  as  the  age  of  arithmetic  that  is  not  appropriate  for  children.  Because  on the one  hand,  early  childhood,  still  in  play.  But  both  of  them  can’t  be  disputed  and  faced resistance.  A  Both  of  them  can  be  bridged  by  their  mathematical  educational  games  in order  to  enhance  the  creativity  of  children.  So  in  early  childhood  should  be  targeted  not cognitive  intelligence  but  the  creativity  of  children.  Therefore,  this  study  will  focus  how  to foster the creativity of children with math games. The approach in this study using literatif study. Is to find various references to give an answer to these problems.  Keywords:  Education, Creativity and Mathematics games